2018
DOI: 10.1186/s12906-018-2268-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hydroalcoholic extract of Juglans regia (walnut) leaves on blood glucose and major cardiovascular risk factors in type 2 diabetic patients: a double-blind, placebo-controlled clinical trial

Abstract: BackgroundWe aimed to evaluate the effects of a hydroalcoholic extract of Juglans regia L. leaves on blood glucose level and cardiovascular risk factors in type 2 diabetic patients.MethodsIn this randomized, double-blind, placebo-controlled, parallel-group (2 arms) clinical trial, 50 diabetic patients were divided into two groups: treatment group (receive the capsules containing 100 mg J. regia leaf extract) and control group (receive the capsules containing placebo, microcrystallin cellulose). Baseline partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…The effect of 50% ethanolic extract prepared from walnut green husk and leaf on cutaneous Leishmaniasis caused by Leishmania major in BALB/c mice were also reported by Sharafi Chegeni, et al [162]. In a double-blind, placebo-controlled clinical trial study reported by Rabiei, et al [173], a hydroalcoholic extract (70%) of walnut leaves was used to evaluate its effects on blood glucose levels in type 2 diabetic patients and the major cardiovascular risk factors.…”
Section: The Solvents Used For the Preparation Of Walnut Extractsmentioning
confidence: 82%
“…The effect of 50% ethanolic extract prepared from walnut green husk and leaf on cutaneous Leishmaniasis caused by Leishmania major in BALB/c mice were also reported by Sharafi Chegeni, et al [162]. In a double-blind, placebo-controlled clinical trial study reported by Rabiei, et al [173], a hydroalcoholic extract (70%) of walnut leaves was used to evaluate its effects on blood glucose levels in type 2 diabetic patients and the major cardiovascular risk factors.…”
Section: The Solvents Used For the Preparation Of Walnut Extractsmentioning
confidence: 82%
“…Groups with the similar alphabet on each column are not significantly different, but different alphabets indicate a significant difference between groups, the label of "ac" means that it has no significant difference with columns labeled as "a" and "c (Delaviz et al, 2017). It can be said that anti-hyperglycemic and hypoglycemic effects of walnut leaf extract are probably due to flavonoids, such as quercetin and kaempferol (Rabiei et al, 2018). Vessal, Hemmati, and Vasei (2003) reported that 10 and 15 mg/kg doses of quercetin had no impact on plasma glucose level in normal animals, but significantly decreased the level of plasma glucose in streptozotocin-induced diabetic rats after 8-10 days, and blood glucose returned to the normal level (Vessal et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Two clinical studies have been conducted in Iran and Brazil, respectively, and the results demonstrated that two different leaf extracts were effective for resolving diabetic symptoms ( Table 8 ). Rabiei et al conducted a study to evaluate the effects of a hydroalcoholic extract of Juglans regia L. leaves on blood glucose level and cardiovascular risk factors in T2DM patients [ 122 ]. The trial was randomized, double-blind, placebo-controlled and parallel-grouped.…”
Section: Type 2 Diabetes and Plant Extractsmentioning
confidence: 99%